Synergistic Effect of Quercetin and Cobalt Ferrite-Graphene Oxide-Based Hyperthermia to Inhibit Expression of Heat Shock Proteins and Induce Apoptosis in Breast Cancer Cells - Fatemeh Mobaraki; Hojjatollah Nazari; Seyed Ali Lajevardiyan; Shadie Hatamie; Hanieh Jafary; Simzar Hosseinzadeh (Tabriz University of Medical Sciences, 2022)
Background: Combinatorial medicine includes promising therapeutic methods for diseases such as cancer, whereby various biochemical and physical agents are simultaneously used to remove tumors. For example, the effectiveness of hyperthermia as a new technique for cancer therapy, can be enhanced, if it is combined with chemical compounds. Herein, the influence of quercetin as a heat shock protein (HSP) inhibitor on the efficiency of cobalt ferrite-graphene oxide (CoFe2O4-GO) nanoparticles-based hyperthermia was investigated in an in vitro study. Methods: Firstly, the surface of graphene sheets was decorated with CoFe2O4 nanoparticles (5-8 nm) and assayed using transmission electron microscopy (TEM), vibrating-sample magnetometer (VSM) and X-ray diffraction (XRD). The cytotoxic effect of the corresponding co-implementation was then examined in MCF7 cell line with or without hyperthermia by (3-(4,5-dimethyl thiazolyl-2)-2,5-diphenyltetrazolium bromide) (MTT) test for 24, 48 and 72 hrs. In addition, the expression of Bax, Bcl2 and HSP70 genes and the production of radicals were evaluated by Real-Time PCR and DPPH (2,2-diphenyl-1-picrylhydrazyl) assays respectively. Results: The study showed that the doses associated with the IC50 points for quercetin and the CoFe2O4-GO nanocomposite were 0.02 mg/ml and 0.001 g/ml, respectively. The results showed that the simultaneous treatment of the cancer cells with quercetin, the nanocomposite, and hyperthermia significantly improves the cytotoxicity effect, increases the expression of Bax gene and down-regulates HSP70 and Bcl2 genes. In addition, the greatest attenuation of DPPH free radicals was observed in the corresponding group. Conclusion: The hybrid treatment of quercetin and the nanoparticle in the presence of hyperthermia could be considered as a promising approach for cancer therapy with minor side effects.